Analysis Of Rotor Cutter Damage On Semi Dull Textile Chips - Martoni; Hirary, Marisa; Prasetya, Adhita (International Journal of Psychosocial Rehabilitation, 2020)
In general, a cutter machine is a cutting tool for cutting large filaments in making chips / plastic pellets. This power motor is capable of moving cutter blades up to 220 rpm, blades designed like starfruit can be used to cut 44 to 66 filament streams. This knife is installed by dealing with a bad knife so that the cutting is more perfect, this often suffers damage to the blade and bad knife, namely the presence of defects or cracks. In addition, this will also make the industry suffer losses in terms of raw materials and blades. To prevent damage from continuing to occur, it is necessary to examine the cause of damage to the cutting blade by conducting tests: hardness test, metallographic test, chemical composition test